Gender Gap or Signs of Patriarchy in the Baltic States:Case of Lithuania - Žvinklienė, Alina (Sociologija. Mintis ir veiksmas, 2009)
Gender issues within the EU are so diverse and differentiated that it is not easy to make valid generalizations even for the Baltic States as a single geopolitical region. However one may say that the tradition of patriarchy was never interrupted either in the Baltic States nor anywhere else. The spirit of patriarchy is imbedded in culture and it consequently affects structures of social institutions as well as individuals, both women and men. In this article gender equality policies in the Baltic States since the twentieth century are discussed. The case of the Baltic States proves again that at present gender equality policies provide the best way forward for democratization of patriarchy although the rhetoric and the formal practice of legal equal rights and opportunities entails more dissembled and sophisticated forms of informal women’s discrimination. The case of Lithuania proves again that only permanent collective efforts of politically active women can influence at least public reflection on gender inequality issues that stimulate authorities to adopt advanced gender equality legislation.
Keywords: patriarchy; feminism; culture; gender politics; gender gap